Are Portuguese consumers ready to understand the risks from pesticide use? - Costa, Cristina Amaro Da (2017)
Understanding consumer perceptions and attitudes towards the use of pesticides in agriculture and its risks is of utmost importance to redirect them towards food products produced in farming systems which use less or no pesticides. Based on data from a survey of 725 Portuguese urban consumers, three groups were identified: non buyers, occasional buyers, habitual buyers, considering their attitudes towards and knowledge of fruit and vegetables from integrated pest management. Knowledge about pesticides and certification systems affects preferences and should be considered as a key issue for market strategies and agricultural policies, and to ensure that consumers are able to define a healthy diet and to understand the influence of their food choices on the environment.